Pelatihan Peningkatan Kualitas Pengawas Internal Koperasi di Provinsi Kalimantan Barat - Ikhsan, Sugiyanto; Hidayat, Udin; Fahreza, Mohammad (E-Coops-Day, 2024)
In an era of economic dynamism and increasingly stringent regulatory demands increasingly stringent regulatory demands, internal supervisors in the context of cooperatives have a very important role in ensuring smooth operations, compliance with role in ensuring smooth operations, compliance with regulations, and effective risk management. rules, and effective risk management. Supervision is a key function of goal-oriented management in other words, supervision is very important to achieve the goals of an organization. important to achieve the goals of an organization. Cooperatives as unique economic entities unique economic entity has its own characteristics, which require reliable and adaptable internal control that is reliable and able to adapt to the dynamics of the business environment. business environment. This condition emphasizes the need to continuously improve quality of internal supervisors to be able to respond to external and internal changes optimally. internal changes optimally. There are several aspects that need to be considered by cooperative supervisors to improve the quality of cooperative internal supervisors, namely regarding compliance and ethics, good governance for cooperatives and risk management. risk management. With the training to improve the quality of cooperative internal supervisors It is expected that cooperative supervisors have managerial, technical, and entrepreneurial skills, so that the entrepreneurial spirit, so that cooperative management reflects a characteristic based on cooperative principles. based on cooperative principles.